1995
DOI: 10.1002/j.1460-2075.1995.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

The product of the nuclear gene PET309 is required for translation of mature mRNA and stability or production of intron-containing RNAs derived from the mitochondrial COX1 locus of Saccharomyces cerevisiae.

Abstract: Expression of the Saccharomyces cerevisiae mitochondrial COX1 locus, which contains several introns and is co‐transcribed with the downstream genes AAP1, OLI2 and ENS2, is controlled by at least 18 nuclear‐encoded proteins. The PET309 gene, encoding one of these proteins, was cloned, sequenced and shown to contain an open reading frame of 965 codons. Isonuclear PET309+ and delta pet309::URA3 strains carrying mitochondrial genomes that differ in the number of COX1 introns, were generated. Analysis of RNA specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
208
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(218 citation statements)
references
References 75 publications
8
208
2
Order By: Relevance
“…(McMullin et al, 1990;Haffter et al, 1991;Haffter and Fox, 1992) and interactions between of Nam1p and Rpo41p (mitochondrial RNA polymerase) (Rodeheffer et al, 2001) were reported previously. Two-hybrid and genetic interactions among Pet54p, Pet122p, and Pet494p were reported previously (Brown et al, 1994;Wiesenberger et al, 1995). without eliminating respiratory complex formation, by in vivo expression of chimeric mRNAs containing 5Ј-UTLs and coding sequences derived from different respiratory complex genes (Mü ller et al, 1984;Fox, 1986, 1988;Poutre and Fox, 1987;Rö del and Fox, 1987;Mulero and Fox, 1993b;Manthey and McEwen, 1995). Thus, although the interactions among translational activators for the core cytochrome c oxidase subunits are likely to confer a selective advantage, they are not absolutely required to form the enzyme.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(McMullin et al, 1990;Haffter et al, 1991;Haffter and Fox, 1992) and interactions between of Nam1p and Rpo41p (mitochondrial RNA polymerase) (Rodeheffer et al, 2001) were reported previously. Two-hybrid and genetic interactions among Pet54p, Pet122p, and Pet494p were reported previously (Brown et al, 1994;Wiesenberger et al, 1995). without eliminating respiratory complex formation, by in vivo expression of chimeric mRNAs containing 5Ј-UTLs and coding sequences derived from different respiratory complex genes (Mü ller et al, 1984;Fox, 1986, 1988;Poutre and Fox, 1987;Rö del and Fox, 1987;Mulero and Fox, 1993b;Manthey and McEwen, 1995). Thus, although the interactions among translational activators for the core cytochrome c oxidase subunits are likely to confer a selective advantage, they are not absolutely required to form the enzyme.…”
Section: Discussionmentioning
confidence: 91%
“…The core of the cytochrome c oxidase complex of mammals and yeast comprises three mitochondrially coded subunits, Cox1p, Cox2p, and Cox3p, and is surrounded by imported subunits coded by nuclear genes (Tzagoloff and Dieckmann, 1990;Tsukihara et al, 1996). Translation of each mitochondrially coded mRNA is specifically activated by distinct nuclear gene products: Pet309p for COX1 (Manthey and McEwen, 1995), Pet111p for COX2 (Mulero and Fox, 1993a,b), and Pet54p, Pet122p, and Pet494p for COX3 (Costanzo and Fox, 1988;Brown et al, 1994). Pet309p, detected as an overproduced epitope-tagged protein, is an integral inner membrane protein partially exposed on the intermembrane space side (outside) (Man-they et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The identified sequence was that of PET309, which encodes a protein required for stability and translation of COX1 mitochondrial mRNA (29). Among the open reading frames present near PET309, we identified an uncharacterized gene that we have named SPC3 (accession no.…”
Section: High Copy Suppression Of Sec11 Reveals the Yeast Homolog Tomentioning
confidence: 99%
“…The rapid loss of respiratory function, even under selective conditions, suggested that the revertants might be heteroplasmic cells containing both the wildtype and suppressor r À genomes. This type of mitochondrial suppressor has been reported for a number of mitochondrial protein-coding genes that fail to be expressed because of mutations in nuclear gene products that promote translation of the mRNAs by interacting with their 59-UTRs (Dieckmann et al 1984;Muller et al 1984;Rodel and Fox 1987;Manthey and McEwen 1995). The presence in W303DATP22/ R3 of a suppressor r À genome was confirmed by the mitochondrial genotypes of 104 respiratory-deficient segregants (Table 3).…”
Section: Resultsmentioning
confidence: 58%
“…Mitochondrial r À genomes with heterologous 59 upstream sequences have been shown to suppress mutations in translation factors for COX1 (Manthey and McEwen 1995), COX2 (Poutre and Fox 1987), COX3 (Muller et al 1984), and COB (Rodel and Fox 1987). These transcript-specific translation factors interact with the 59-UTRs of their cognate mRNAs.…”
Section: Discussionmentioning
confidence: 99%